When the past meets the present: the oldest known Bibioninae, and the youngest known Cretobibioninae (Diptera, Bibionidae) from mid-Cretaceous Myanmar amber - Skartveit, John (Zootaxa, 2023)
The Diptera family Bibionidae has a rich fossil record from the Tertiary, however little is known about this family in the Mesozoic. Recently, a number of specimens have been found in mid-Cretaceous Myanmar amber, dating from about 99 MYr BP. I report the finding of the oldest known member of the recent subfamily Bibioninae, as well as the youngest known member of the Cretaceous subfamily Cretobibioninae.The Cretobibioninae is represented by Cretobibio burmiticus sp. n., which suggests a wide, possibly cosmopolitan distribution of the recently discovered subfamily Cretobibionidae, the Bibioninae by Protodilophus semispinosus gen. et sp. n. The latter species is probably related to the recent and Tertiary genus Dilophus, but displays some plesiomorphic traits related to the more recent taxa.